Anaplasmataceae: Dichotomous Autophagic Interplay for Infection - Patterson, LaNisha L.; Byerly, Caitlan D.; McBride, Jere W. (Frontiers in Immunology, 2021)
Autophagy is a vital conserved degradative process that maintains cellular homeostasis by recycling or eliminating dysfunctional cellular organelles and proteins. More recently, autophagy has become a well-recognized host defense mechanism against intracellular pathogens through a process known as xenophagy. On the host-microbe battlefield many intracellular bacterial pathogens have developed the ability to subvert xenophagy to establish infection. Obligately intracellular bacterial pathogens of the Anaplasmataceae family, including Ehrlichia chaffeensis, Anaplasma phaogocytophilium and Orientia tsutsugamushi have developed a dichotomous strategy to exploit the host autophagic pathway to obtain nutrients while escaping lysosomal destruction for intracellular survival within the host cell. In this review, the recent findings regarding how these master manipulators engage and inhibit autophagy for infection are explored. Future investigation to understand mechanisms used by Anaplasmataceae to exploit autophagy may advance novel antimicrobial therapies and provide new insights into how intracellular microbes exploit autophagy to survive.